Effectiveness of Early Mobilization and Administration of Cork Fish Extract on Wound Healing of Sectio Caesarean Surgery at Noemuti Health Center - Fitriyaningsih, Fitriyaningsih; Sepeh, Yandri Ratu; Gudino, Isabel De Fatima; Simbolon, Meteria (International Journal Papier Advance and Scientific Review, 2024)
This study aims to determine the effectiveness of early mobilization and administration of cork fish extract on wound healing after Sectio caesarea surgery at Puskesmas Noemuti. The problem faced is the high rate of cesarean delivery in Indonesia which can cause complications such as surgical wound infection and increase maternal and infant mortality. The method used is a type of quasy experimental research with a static group comparison design approach. The results showed that early mobilization and administration of cork fish extract were effective in improving sectio caesarean wound healing. The treatment group given the intervention of early mobilization and administration of cork fish extract had a better level of surgical wound healing compared to the control group which was only given the standard hospital intervention. This study can contribute to improving the quality of health services in Indonesia, especially in the handling of labor through cesarean section.